The impact of authoritative parenting style on children’s academic achievements in Domboshava Community. (ZIMCRODO Cluster). - Dewa, Themba (Midlands State University, 2017)
The impact of authoritative parenting style on children’s academic achievements in Domboshava community was the prime focus of this research. Descriptive research design was used in the collection of data. The research questions highlighted and addressed the challenges which are faced by students who live in an authoritarian family. Research questions also assessed the impact of authoritative parenting on children’s performance. From the interviews conducted it was seen that there are a number of factors which affect children’s academic achievement which include the availability of resources and the school environment but these are outweighed by the influence of parents.